1986
DOI: 10.1001/archotol.1986.03780090030004
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin (Somatostatinlike) Immunoreactive Cells in the Human Inner Ear

Abstract: \s=b\Certain epithelia of the human inner ear and human endolymphatic sac display somatostatin and/or somatostatinlike immunoreactivity. Histologic sections from 13 human temporal bones and from 15 endolymphatic sacs were studied using the unlabeled antibody peroxidaseantiperoxidase technique. The somatostatin and/or somatostatinlike immunoreactive cells were located exclusively in the covering epithelium of the spiral prominence and in the epithelium of the intermediate and rugosal part of the endolymphatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
4
16
0
Order By: Relevance
“…le, inset). These findings are in accordance with previously published observations on cells in the human ES containing neurosecretory granules and somatostatin [8],…”
Section: Resultssupporting
confidence: 94%
“…le, inset). These findings are in accordance with previously published observations on cells in the human ES containing neurosecretory granules and somatostatin [8],…”
Section: Resultssupporting
confidence: 94%
“…In a previous study, we have reported the presence of secretory immunoglobulin A (IgA) in the human ES [4,5]. Immunohisto chemical findings support the assumption that the human ES, like the gut, appears to have not only resorptive and secretory, but also immunologic and paracrine functions [2,[4][5][6], The present immunohistochemical study was designed to identify cells with immuno logical functions in the extraosseous part of the human ES.…”
Section: Introductionsupporting
confidence: 54%
“…It has been demonstrated that somatostatin immunoreactive cells can be found in the human inner ear, implicating a role of the somatostatinergic system in the inner ear. 20 Based on the analogy between the retina and the inner ear and the fact that somatostatin can be detected in the inner ear, we tested in this study whether somatostatin receptors are present within the cochlea and whether somatostatin is able to protect auditory hair cells from gentamicin-induced apoptotic cell death in vitro.…”
mentioning
confidence: 99%